PhET SIMULATION: A PLATFORM TO IMPROVE STUDENTS PERFORMANCE IN CHEMISTRY CONTENT - Ibrahim, Abdulmuhsin; Bolaji, Hameed Olalekan; Oyeyemi, Waheed Tunde (Journal of Chemistry Education and Integration, 2025)
This research investigates the impact of PhET simulations on improving students' performance in Chemistry. A quasi-experimental design was employed, involving pre-test, post-test, and control groups. The study targeted senior secondary school students in Kwara State, Nigeria, using purposively selected intact classes from two schools. Students were grouped based on their prior academic performance. To assess learning outcomes, PhET simulations and a Chemistry Performance Test (CPT) were utilized. The instruments underwent expert validation for accuracy, and their reliability of 0.79 was confirmed through Cronbach's Alpha. Findings revealed that the experimental group showed a marked improvement in post-test scores compared to the control group, highlighting the effectiveness of PhET simulations in improving students' understanding and retention of Chemistry concepts